Penguatan Literasi Digital Siswa SMA/SMK melalui Pelatihan Produksi Konten Digital di Purwokerto - Alfizi Alfizi; Yadi Fakhruzein Terang Jaya; Colin Rafael Damario (Lembaga Pengembangan Kinerja Dosen, 2026)
The intensive use of social media among students needs to be directed toward productive, creative, and responsible activities. This community service program aimed to strengthen digital literacy and content production skills among senior and vocational high school students through digital content production training. The program was conducted on June 20, 2026, at Computer Laboratories 1 and 2, Campus 2 of Universitas Harapan Bangsa, Purwokerto, involving 22 students from senior and vocational high schools in the Purwokerto area. A participatory training approach was employed through lectures, demonstrations, guided practice, mentoring, and feedback. The materials covered the role of Content Creators, content ideation and planning, audio-video editing, and social media optimization. The program was evaluated descriptively through observations of participant engagement, completion of practical activities, responses to mentoring, and activity documentation. The results showed that all planned sessions were successfully implemented and participants were actively involved throughout the program. They were able to follow the stages of idea development, operate relevant devices and applications, perform basic audiovisual editing, and understand social media as a medium for communication, promotion, and self-development. The program also created a collaborative learning environment, encouraged participants to express their ideas confidently, and strengthened awareness of positive digital media use. Therefore, digital content production training provided meaningful benefits in developing more creative, adaptive, and productive students in the digital era.